2014
DOI: 10.1080/19768354.2014.905491
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid decreases cell proliferation and migration in the cerebellum of zebrafish larvae

Abstract: Valproic acid (VPA) is used as an antiepileptic drug or mood stabilizer. Recent studies have shown that exposure to VPA during embryonic development alters neural progenitor cell proliferation. The main goal of this investigation was to elucidate the effects of VPA on cell proliferation in the cerebellum of zebrafish larvae using immunohistochemistry. 5-bromo-2'-deoxyuridine (BrdU) and proliferating cell nuclear antigen (PCNA)-labeled cells were mostly found in the ventral cerebellum proliferation zone and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…We demonstrated that VPA exposure reduced the number of neuronal progenitor cells in Tg( nestin:GFP ) embryos. This result is congruent with previous findings showing that VPA exposure decreases the proliferation of neuronal progenitor cells in the telencephalon 42 and cerebellum 37 of larval zebrafish brain. It remains largely unclear how VPA affects the proliferation of neuronal progenitor cells in the brain; the decrease in progenitor cells may result from drug‐induced apoptosis 37 or inhibition of cell proliferation 42 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We demonstrated that VPA exposure reduced the number of neuronal progenitor cells in Tg( nestin:GFP ) embryos. This result is congruent with previous findings showing that VPA exposure decreases the proliferation of neuronal progenitor cells in the telencephalon 42 and cerebellum 37 of larval zebrafish brain. It remains largely unclear how VPA affects the proliferation of neuronal progenitor cells in the brain; the decrease in progenitor cells may result from drug‐induced apoptosis 37 or inhibition of cell proliferation 42 .…”
Section: Discussionsupporting
confidence: 93%
“…36 Next, we demonstrated that VPA exposure increased the hindbrain midline gap in developing zebrafish embryos. This malformation might be caused by a reduction in neuronal cell migration, 37 or might be described as a cranial NTD that is analogous to human fetal VPA-related cranial NTDs. 38 Further studies will be required to make a distinction between these mechanisms.…”
Section: F I G U R Ementioning
confidence: 99%
“…This coincides with the period of VPA exposure in this study, suggesting that the drug has significant effects on cellular organization during cerebellar histogenesis. The observed behavioral and morphological phenotypes align with characteristics associated with ASD, such as reduced brain size and dysregulation of neuronal proliferation and migration [62][63][64][65][66].…”
Section: Discussionsupporting
confidence: 60%
“…According to previous studies, VPA suppresses cell proliferation, delays cell cycle, and induces apoptosis in vitro and in vivo (Michaelis et al 2004;Chen et al 2006;Lee et al 2014;Zhu et al 2015). Our study showed that, compared to the control, the cell proliferation in the mesenchymal compartment of the regenerated caudal fin was significantly decreased in VPA-treated zebrafish.…”
Section: Discussionmentioning
confidence: 92%